Neuroscience Media in Arabic Teaching: Fun and Easy for Students / Media Neuroscience Dalam Pengajaran Bahasa Arab: Menyenangkan dan Mudah Bagi Siswa - Mohammad Jailani; Djamaludin Perawironegoro; Yoyo (al Mahāra: Jurnal Pendidikan Bahasa Arab, 2021)
The development of the Arabic language curriculum is increasingly following the Ministry of Religion curriculum. On the one hand, the teacher has not been innovative in teaching the material to students. This study aims to analyze neuroscience-based Arabic learning media at SMK Muhammadiyah 3 Yogyakarta. This type of research uses qualitative methods, and the nature of this research is to seek accurate and total information at SMK Muhammadiyah 3 Yogyakarta. The subjects of this study consisted of students and teachers of class X. The object of this research was teaching Arabic at SMK Muhammadiyah 3 Yogyakarta. Data collection techniques were carried out by interview, observation, and documentation methods. data validity using triangulation. Data analysis uses the Miles and Huberman model, namely data reduction, data display, and conclusion drawing/verification data. The results of the study prove that Neuroscience-based Arabic learning media responds to students in facilitating learning Arabic, accelerating vocabulary memorization (mufrodat), and practicing reading, writing, listening, and speaking (muhadasah), during the COVID-19 period. The implications of this learning media, as an alternative to understanding mufrodat and muhadasah online learning during the COVID-19 period and in the face-to-face period. Because the media that is taught to students makes it easy, and fun. Keywords: Arabic, COVID-19, Theacing Media, Neuroscience. Abstrak Pengembangan kurikulum bahasa Arab semakin maju mengikuti kurikulum Kemenag. Di satu sisi guru belum berinovatif dalam mengajarkan materi kepada siswa. Penelitian ini bertujuan menganalisis media pembelajaran bahasa Arab berbasis neurosains di SMK Muhammadiyah 3 Yogyakarta. Jenis penelitian ini menggunakan metode kualitatif, serta sifat penelitian ini mencari informasi secara akurat dan totalitas di SMK Muhammadiyah 3 Yogyakarta. Subjek penelitian ini terdiri dari siswa dan guru kelas X. Objek penelitian ini adalah pengajaran bahasa Arab di SMK Muhammadiyah 3 Yogyakarta. Teknik pengumpulan data dilakukan dengan metode wawancara, observasi, dan dokumentasi. keabsahan data menggunakan triangulasi. analisis data menggunakan model Miles dan Huberman, yaitu dengan data reduction, data display, dan data conclusion drawing/verification. Hasil penelitian membuktikan bahwa media pembelajaran Bahasa Arab berbasis Neurosains merespons peserta didik dalam memudahkan belajar Bahasa Arab, mempercepat penghafalan kosa kata (mufrodat) dan praktek membaca, menulis, mendengar, serta berbicara (muhadasah), di masa COVID-19. Implikasi media pembelajaran ini, sebagai alternatif pemahaman mufrodat dan muhadasah pembelajaran online di masa COVID-19 dan di masa tatap muka. Karena media yang adiajarkan kepada siswa memudahkan, dan menyenangkan. Kata kunci: Bahasa Arab, COVID-19, Media Pengajaran, Neurosains.